Antiarrhythmic Mechanisms of SK Channel Inhibition in the Rat Atrium. Issue 2 (August 2015) - Skibsbye, Lasse; Wang, Xiaodong; Axelsen, Lene Nygaard; Bomholtz, Sofia Hammami; Nielsen, Morten Schak; Grunnet, Morten; Bentzen, Bo Hjorth; Jespersen, Thomas
Abstract : Introduction: SK channels have functional importance in the cardiac atrium of many species, including humans. Pharmacological blockage of SK channels has been reported to be antiarrhythmic in animal models of atrial fibrillation; however, the exact antiarrhythmic mechanism of SK channel inhibition remains unclear. Objectives: We speculated that together with a direct inhibition of repolarizing SK current, the previously observed depolarization of the atrial resting membrane potential (RMP) after SK channel inhibition reduces sodium channel availability, thereby prolonging the effective refractory period and slowing the conduction velocity (CV). We therefore aimed at elucidating these properties of SK channel inhibition and the underlying antiarrhythmic mechanisms using microelectrode action potential (AP) recordings and CV measurements in isolated rat atrium. Automated patch clamping and two-electrode voltage clamp were used to access INa and IK, ACh, respectively. Results: The SK channel inhibitor N-(pyridin-2-yl)-4-(pyridin-2-yl)thiazol-2-amine (ICA) exhibited antiarrhythmic effects. ICA prevented electrically induced runs of atrial fibrillation in the isolated right atrium and induced atrial postrepolarization refractoriness and depolarized RMP. Moreover, ICA (1–10 μM) was found to slow CV; however, because of a marked prolongation of effective refractory period, the calculated wavelength was increased. Furthermore, at increased pacing frequencies, SK channel inhibition by ICA (10–30 μM) demonstrated prominent depression of other sodium channel–dependent parameters. ICA did not inhibit IK, ACh, but at concentrations above 10 μM, ICA use dependently inhibited INa . Conclusions: SK channel inhibition modulates multiple parameters of AP. It prolongs the AP duration and shifts the RMP towards more depolarized potentials through direct ISK block. This indirectly leads to sodium channel inhibition through accumulation of state dependently inactivated channels, which ultimately slows conduction and decreases excitability. However, a contribution from a direct sodium channel inhibition cannot be ruled. We here propose that the primary antiarrhythmic mechanism of SK channel inhibition is through direct potassium channel block and through indirect sodium channel inhibition. Abstract : Supplemental Digital Content is Available in the Text.